Adenoma Detection Rate in Colonoscopic Screening with Ketamine-based Sedation: A Prospective Observational Study - Mirza KOVACEVIC; Nermina RIZVANOVIC; Adisa SABANOVIC ADILOVIC; Nedim BARUCIJA; Anida ABAZOVIC (Medeniyet Medical Journal)
Objective: This study aimed to determine the relationship between one of the most commonly used anesthesia techniques, ketamine-based sedation, on the value of adenoma detection rate (ADR) during colonoscopy screening. Methods: This prospective, observational study included 140 patients, who underwent a standard colonoscopy preparation before the procedure. Sedation regimens included ketamine at 0.5 mg/kg and propofol at 0.5 mg/kg. Additional doses of propofol were administered at 0.5 mg/kg to maintain the Ramsey Sedation scale. Baseline characteristics, ADR, bowel preparation quality according to the Chicago bowel preparation (CHBP) scale, cecal intubation, colonoscopy removal, and complications were analyzed. Results: The mean age of patients was 55.76 years; 40 (28.6%) were males and 100 (71.4%) were females. The ADR was 43.57%, wherein 15.71% in males and 27.86% in females. There were 43.6% adenomas, 17.9% biopsies, and 22.9% polypectomies. The largest location of adenomas/polyps were in the rectum and sigmoid and ascending colon (p=0.11), a biopsy of the sigmoid colon and ileum (p<0.05), polypectomy of the rectum and sigmoid and ascending colon (p<0.05). The cecal intubation was 93.6% with a withdrawal time that is >6 min in most patients (80%) (p<0.05). The CHBP scale showed good bowel preparation (p<0.05) without complications. Conclusions: Ketamine-based sedation is in good overall correlation with ADR. Therefore, the sedation technique should be included for ADR assessment in the future.